PERSEPSI KHALAYAK TERHADAP ISI PESAN DALAM TAYANGAN FILM ANIMASI UPIN DAN IPIN DI MNC TV - Oktavianti, Dhini (Universitas Prof. Dr. Moestopo (Beragama), 2012)
Television is powerfull mass media that can be influence the audiences specially children. Animation movies are not always for children. Parent have to pay attention on the message of the animation movies for their children. Upin and Ipin movies is different from other animation movies. It is carry asia value dan religion value. This research about perceptions message in Upin and Ipin animations movies on MNC TV. Research method is kualitative descriptive that uses survey for collecting data.Â Perceptions theory, individual differences theory, and social categories theory.